Impact of cystic fibrosis on pediatric oral health: a comprehensive review - Ahmed, Neveen M.; Aljarallah, Faisal A.; Bouges, Sara F.; Almagasslah, Heba J.; Abughazalah, Omair; Areesh, Reem M.; Dabbour, Laila A.; Bahdad, Maria O.; Alansari, Bashair O.; Alrashidi, Albandari G.; Alnukhaylan, Layan T. (International Journal Of Community Medicine And Public Health, 2025)
Cystic fibrosis (CF) is a complex genetic disorder that affects multiple systems, including the oral cavity. In children, CF leads to unique challenges in maintaining oral health due to the interplay of systemic factors, dietary requirements, and medical treatments. Alterations in salivary flow and composition, often observed in CF patients, contribute to an increased risk of xerostomia, enamel erosion, and periodontal disease. These issues are further exacerbated by high-calorie, carbohydrate-rich diets prescribed to manage metabolic needs, creating a favorable environment for caries development. The use of inhaled corticosteroids, nebulized antibiotics, and other essential medications introduces additional oral health challenges, such as fungal infections and changes in the oral microbiota. Gastroesophageal reflux disease, a common comorbidity in CF, contributes to dental erosion through repeated exposure to gastric acids. Despite these risks, frequent use of antibiotics in CF patients has shown a paradoxical reduction in dental caries prevalence, highlighting the complex oral microbial dynamics in this population. Preventive strategies include dietary counseling, regular fluoride application, and tailored oral hygiene routines, such as the use of electric toothbrushes and interdental brushes. Therapeutic interventions focus on minimally invasive techniques, fluoride-releasing restorative materials, and the application of sealants to protect vulnerable tooth surfaces. Collaboration among dentists, pediatricians, dietitians, and CF specialists is crucial to address the multifactorial challenges and improve both oral and systemic outcomes. The relationship between cystic fibrosis and oral health underscores the importance of integrating dental care into the broader management of CF. Early identification of oral complications and the implementation of personalized prevention and treatment strategies can significantly enhance the quality of life for pediatric CF patients while reducing the long-term burden of oral diseases.